Libertarian Critiques of Consent in Sexual Offences - Stephen Knight (UCL Journal of Law and Jurisprudence, 2011)
This paper uses a system of moral principles derived from Alan Gewirth's Principle of Generic Consistency to demonstrate both the moral necessity of adopting a libertarian approach to consent in sexual offences, and that such an approach is practically superior with regard to the policy objectives which English law seeks to pursue in this field. The paper achieves this through inquiring into the state of contemporary English law and then analysing its political and philosophical underpinnings on a diverse range of issues, from uncomplicated consent through to coercion, informed consent, and the age of consent. In each case alternatives are proposed which would remedy the moral and practical deficiencies in English law. However, the paper concludes that remedying the defects in English law is only an interim solution, and that no true answer to the contradictions which the law faces is possible without a wholesale rejection of the socio-economic oppression which the greater part of humanity face under capitalism. In light of this, the author takes the view that the sexual autonomy of all agents can only be preserved through a transition to a libertarian and socialist society. Read more